Preventive Measures and Active Response against COVID-19 Taken by All Four Provinces, Two Independent Territories, and the Federal State of Islamic Republic of Pakistan, Islamabad. Issue 4 (19th May 2022) - Imran, Muhammad; Ahmad, Bashir; Maqbool, Farhan; Ahmad, Ashfaq; Malik, Arshad; Aziz, Shahid; Rasheed, Faisal; Akhter, Tayyab Saeed
ABSTRACT: The novel coronavirus disease outbreak started in December, 2019 in Wuhan, China. On March 11, 2020, WHO declared COVID-19 outbreak as a pandemic due to uncontrolled situation. Pakistani government management against COVID-19 was excellent having 204.65 million population, all four provinces, two independent territories, and federal state took different initiative in pandamic situation c. that's why the situation was under control in Pakistan due to state respond urgently to halt the spread of disease. With rapid response and full support of the government of Pakistan, the situation was under control in all aspects of life, June 17, 2019, each district of Pakistan recorded at least one confirmed case of COVID-19 due to remarkable effort against pandemic. The state of Pakistan declare urgency and fastest action to control the situation, economic package, ventilator manufacturing, and diagnostic kits were manufactured locally. The DRAP Pakistan permitted to use different drugs against COVID-19 and purchased vaccines from China. Due to the planning and management of the Pakistani Government, the situation was under control as compared with neighborhood countries (China and India), in both countries COVID-19 waves was lethal.